Transforming growth factor 1, ras and p53 in silica-induced fibrogenesis and carcinogenesis - Williams, AO; Saffiotti, U (Scandinavian Journal of Work, Environment & Health, 1995)
The pathogenesis of mesenchymal and epithelial lung reactions was studied after a single intratracheal instillation of quartz into rats. Relationships between transforming growth factor βl (TGF-β1) and the ras and p53 genes were investigated in silicosis and associated lung cancer. Immunohistochemical reactivity to mature TGF-β1 was localized intracellularly in fibroblasts and macrophages at the periphery of silicotic granulomas and in stroma adjacent to hyperplastic alveolar type II cells and extracellularly in connective tissue matrix adjacent to hyperplastic alveolar type II cells. TGF-β1 precursor was localized intracellularly in hyperplastic alveolar type II cells adjacent to granulomas and in the cells of adenomas, but not in carcinomas. Hematite-treated controls showed no reactivity to TGF-β1. mmunohistochemical localization of pan-reactive p21 ras protein in quartz-treated rat lungs was increased in hyperplastic alveolar type II cells adjacent to granulomas, but not in adenomas and carcinomas. Foci of nuclear immunoreactivity to p53 protein were observed in 25% of the carcinomas.
Keywords: p53; alveolar type II cells; immunohistochemistry; p21 ras; rat; TGF-beta1